Microwave ring circuits and antennas - Chang, Kai (Wiley series in microwave and optical engineering, 1996)
Counter Microwave ring circuits are remarkably simple in design and their performance is usually easy to predict. Because of these advantages, they are common components in everything from measurements to filters, oscillators to antennas, mixers to frequency selective surfaces. Yet despite their many uses, up until now a clear and detailed description of these vital components could be obtained only by sifting through numerous papers and books. Microwave Ring Circuits and Antennas provides the first fully dedicated treatment of ring circuits, with the aims of promoting a greater understanding of their design and operation and stimulating further applications. Based on ten years of research results and publications by the author and his students, as well as the work of other professional groups, Dr. Chang's text covers most ring resonators and cavities as they are utilized in a variety of transmission lines, including microstrip, slotline, coplanar waveguide, and waveguide. Microwave Ring Circuits and Antennas begins with a general introduction to the ring circuit, its history, as well as its past and present applications. It then provides a general description of simple models, field analysis, transmission line models, modes, perturbation methods, and coupling methods of ring resonators. The author introduces electronically tunable and switchable ring resonators, which can be achieved by incorporating varactor and PIN diodes into the ring circuits. Major coverage is devoted to the applications of ring resonators to microwave measurements, filters, couplers, and magic-T's. The final chapters offer a concise discussion of ring antennas and frequency selective surfaces, as well as a broad survey of the potential applications of ring circuits in mixers, active antennas, oscillators, and optoelectronics. Throughout the text, practical applications are clearly illustrated with figures and actual performances.